2013
DOI: 10.1093/heapol/czt059
|View full text |Cite
|
Sign up to set email alerts
|

Improving and sustaining quality of child health care through IMCI training and supervision: experience from rural Bangladesh

Abstract: IMCI training coupled with regular supervision can sustain improvements in the quality of child health care in first-level health facilities, even among workers with minimal pre-service training. These findings can guide government policy makers and provide further evidence to support the scale-up of regular supervision and task shifting the management of sick under-five children to lower-level service providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
3
26
0
Order By: Relevance
“…Our findings add to the existing literature 30 32 and indicate that supportive supervision can improve both adherence to clinical guidelines and the overall quality of care.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our findings add to the existing literature 30 32 and indicate that supportive supervision can improve both adherence to clinical guidelines and the overall quality of care.…”
Section: Discussionsupporting
confidence: 72%
“…In our study and a study in Kenya, 30 the supportive supervision team comprised paediatricians; of two trials performed in primary care, the providers were paediatricians in one 31 and medical officers and staff supervising the Integrated Management of Childhood Illness in the other 32 . The characteristics of the ideal provider may depend on who is receiving supportive supervision: adequately trained medical officers may be able to provide effective supportive supervision to primary care staff, whereas a team of experienced paediatricians may be needed for hospital staff.…”
Section: Discussionmentioning
confidence: 99%
“…We found that a standard, 4-day, WHO training course followed by periodic supportive supervision from national, trained paediatricians every 2 months for 1 year significantly reduced inappropriate case management of hospitalized children and improved the overall quality of paediatric care. Our findings add to the existing literature [30][31][32] and indicate that supportive supervision can improve both adherence to clinical guidelines and the overall quality of care.…”
Section: Discussionsupporting
confidence: 72%
“…Randomized trial evidence has shown positive effects of supervision on care for children under-5 using IMCI (Hoque et al 2014, Pariyo et al 2005b, Kayemba Nalwadda et al 2013, Amaral et al 2004) for general primary care (including vaccination, vitamin A distribution, family planning, antenatal care, and costs per capita) (Loevinsohn et al 1995) and primary eye care (Okwen et al 2014). Plausibility trial evidence also supports the association of increased or enhanced supervision with quality of immunization services (Djibuti et al 2009), STI services (Mugala et al 2010), malaria care and treatment (Zurovac et al 2004), management of childhood diarrhoea (Pham DM et al 2013), and correct use of pharmaceuticals from front-line dispensaries (Ross-Degnan D et al 2007).…”
Section: Resultsmentioning
confidence: 99%